Development and Validation of the Norfolk Quality of Life Fatigue Tool (QOL-F), a New Measure of Perception of Fatigue - Vinik, Etta J. (J Am Med Dir Assoc, 2019)
OBJECTIVES: Design a questionnaire able to evaluate and distinguish between cognitive and physical aspects of fatigue in different age groups of “non-diseased” people, to guide appropriate prevention and interventions for the impact of frailty that occurs in normative aging. STUDY DESIGN/ PARTICIPANTS: Develop the Norfolk QOL-Fatigue (QOL-F) with items of cognitive and physical fatigue, anxiety, and depression from validated questionnaires including items from Patient/Reported/Outcomes/Measure/Information/System (PROMIS) databank. Administer the preliminary QOL-F to 409 healthy multi-ethnic local participants (30 to 80yrs) divided into five age-groups. METHODS: We distilled the item pool using exploratory (EFA) and confirmatory factor analysis (CFA). EFA identified five latent groups as possible factors related to: problems from fatigue, subjective fatigue, reduced activities, impaired activities/of/daily/living (ADLs), and depression. RESULTS: CFA demonstrated good overall fit (χ2(172)=1094.23, p<.001; TLI=.978; RMSEA=.049) with factor loadings >.617 and strong inter-factor correlations (.69 to .83) suggesting that fatigue in each domain is closely related to other domains and to overall scale except for ADLs. Five-factor solution displayed good internal consistency (Cronbach’s α=.78 to .94). Total and domain scores were fairly equivalent, in all age/groups except for 40–49 year/ old group who had better overall scores. The 70–79 year/olds had better ADLs scores. In item response analysis, factor scores in the different age groups were similar, so age may not be a significant driver of fatigue scores. Fatigue scores were significantly higher in females than in males (p<.05). CONCLUSIONS: Fatigue is a perceived cognitive phenomenon rather than an objective physical measure. The Norfolk QOL-F tool, comprised of 35 items and five domains is sensitive to aging, cognitive and emotional function and able to distinguish a unique subset of ostensibly normal 40–49 year/olds with better QOL-F scores than other age groups. Importantly, 70–79 year/olds had better ADLs scores indicating potential benefit from physical, balance and cognitive interventions.